Аналіз критерії надійності будівельної техніки та функціонально-технічних показників їхніх механізмів - Назаренко, М. І.; Король, В. І. (Техніка будівництва, 2020)
In the paper there is the analysis of existing methods of choice and calculations of indicators of reliability. There are indicators which have the priority to assess the reliability of construction machinery. There is made the analysis of passport data of more than 160 models of tower cranes, which are produced by world leading manufacturers such as Liebherr, Jaso, Terex, Potain. Based upon received data there were made graphs and certain equations of correspondences of constructive weight of the crane and total engine of power capacity of the crane. These equations constitute a recommendation to determine an approximate value of constructive mass and total engine power for cranes of various capacities.